Arahan Desain Fasad Koridor Jalan Songoyudan untuk Memperkuat Citra Visual Area Perdagangan Bersejarah di Surabaya - Rizqiyah, Fardilla (EMARA Indonesian Journal of Architecture, 2016)
Songoyudan road corridor is an essential corridor in the area of CBD I which is located in the Old Town of Surabaya. As a commercial corridor, it is filled by rows of shophouses that sells both variety of goods and secondary needs of most citizens in Surabaya. Initially, the existing buildings are the dutch heritage building which were converted into a shophouses. Yet, there are several shop buildings that has been renovated and reconstructed by the owner into a modern style building. As a corridor which is located both in the developing region and high density of activity, the reducing of the colonial heritage buildings is feared to eliminate the visual distinctiveness of the region. This can also be an unfavorable precedent for other buildings owners when renovating or reconstructing their buildings. So that, their vulnerable heritage building will be reconstructed into a new modern style building that can eliminate the historical value in it. This study aims to find an alternate facade design of shophouses in the corridor as a commercial building which can be used as a reference in designing a new one. The used methodology is descriptive qualitative through technical analysis of visual character of colonial buildings. The elements observed included style, color, texture, pattern, and scale of the building. These findings are expected to provide a guidance to the community, including architects and building owners in reconstructing the existing shophouses especially in the road corridors of Songoyudan and generally in the area of the Old Town Hall Kembang JepunÂ Surabaya.